Considerations for effective science communication - Steven J. Cooke; Austin J. Gallagher; Natalie M. Sopinka; Vivian M. Nguyen; Rachel A. Skubel; Neil Hammerschlag; Sarah Boon; Nathan Young; Andy J. Danylchuk (Canadian Science Publishing, 2017)
It is increasingly common for scientists to engage in sharing science-related knowledge with diverse knowledge users-an activity called science communication. Given that many scientists now seek information on how to communicate effectively, we have generated a list of 16 important considerations for those interested in science communication: (1) Define what science communication means to you and your research; (2) Know-and listen to-your target audience; (3) Consider a diverse but coordinated communication portfolio; (4) Draft skilled players and build a network; (5) Create and seize opportunities; (6) Be creative when you communicate; (7) Focus on the science in science communication; (8) Be an honest broker; (9) Understand the science of science communication; (10) Think like an entrepreneur; (11) Don't let your colleagues stop you; (12) Integrate science communication into your research program; (13) Recognize how science communication enhances your science; (14) Request science communication funds from grants; (15) Strive for bidirectional communication; and (16) Evaluate, reflect, and be prepared to adapt. It is our ambition that the ideas shared here will encourage readers to engage in science communication and increase the effectiveness of those already active in science communication, stimulating them to share their experiences with others.